Functional outcome of arthroscopic Bankart repair for anterior shoulder instability based on suture anchor configuration - Ballal, Madan; Jayakumar, Tarun (International Journal of Research in Orthopaedics, 2020)
Background: The objective of the study was to evaluate the functional outcome of arthroscopic Bankart repair for anterior shoulder instability to assess whether the number and position of suture anchors plays a role in determining the functional outcome. Methods: This was a prospective study on 32 patients operated with arthroscopic Bankart repair between December 2017 to April 2019. Pre-op and regular follow-up scores were measured at 1 month, 3 months and 6 months post-op using Rowe score and American Shoulder and Elbow Surgeons score to assess functional outcome. Results: Mean age of the study group was 24.5±6.9 years. Functional outcome as determined by Rowe score and ASES score at 6 months follow-up were found to be 90.5±7.2 and 85.9±14.1 respectively when compared to the pre-op scores of 23.2±8.2 and 47.9±5.7 respectively; all of which showed highly significant functional improvement with highly significant reduction in visual analog scale (VAS) pain score. Patients had no recurrent dislocations with mean external rotation limitation of 5o. 25 (78.1%) patients had two suture anchors inserted and 7 (21.9%) patients had multiple (>2) anchors; and when analysis was done, there was no statistically significant difference between number of suture anchors used with respect to the functional scores. Conclusions: We conclude that arthroscopic Bankart repair is a useful and successful procedure. Patient identification and selection remains the key in determining the success of repair. Meticulous surgical technique and correct positioning of suture anchors may help in reducing the number of anchors without compromising on the final functional outcome, thereby reducing the economic burden on patients.